Assessment of Data Over 3G and 4G LTE Networks in Ibadan Metropolis, Nigeria - Olasunkanmi, Oluwaseun Joel; Awofolaju, Tolulope Tola; Emmanuael, Olowookere Oluwasomidotun (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2024)
The routes plied are situated in Ibadan, Oyo State, Nigeria with different longitude and latitude respectively to assess the signal quality of 3G and 4G networks, compare four service/network providers in terms of coverage, service quality with respect to location, and determine areas with weak strength that needs optimization of different operators. The relevance of this study is to provide information as regards each operator in order to provide solution and to educate the subscribers for proper fixed or dynamic internet usage and voice calls. The work would benefit users within the city and the network providers. The mast is built in a sectorial way so that it could serve the arc and has a monitoring neighbor BTS (Base Transceiver Station) in sectorial way so it can circulate the area, though during the test, it was noticed that there are some areas with no monitoring neighbor BTS. The results show the received signal strength indicator (signal strength quality) of each network provider.